Pengaruh Resilience dan Self-Efficacy Terhadap Work Engagement Dimediasi oleh Psychological Empowerment - Risma Indriyanti; Ketut Sunaryanto (Economic Reviews Journal, 2026)
Low levels of Work Engagement in the manufacturing sector have the potential to disrupt operations, reduce product quality, and increase the risk of company losses. This study aims to analyze the direct and indirect effects on Work Engagement of employees in the food manufacturing industry in Tangerang. The research method used is quantitative, data analysis using PLS-SEM with a purposive sampling technique on 170 respondents. The results show that Resilience has a positive effect on Psychological Empowerment, Self-Efficacy and Work Engagement. Psychological Empowerment and Self-Efficacy also have a positive and significant effect on Work Engagement. The mediating role of Psychological Empowerment in the relationship between Resilience and Work Engagement has a positive and significant influence. Further research is recommended to add other variables not yet included in this study, expand the scope of the sample, and increase the sample size for reliability and generalization of the findings. The results of this study help contribute to what management needs to strengthen employee work engagement, especially in the food manufacturing industry.